Study on the formation mechanisms and stability of a gently inclined and shallow accumulative landslide - Mengxiao Zhang; Weizao Wang; Yinbo Hao; Xiaoyang Liu; Ruisong Zhang; Zhaomin Tian; Minuo Huang; Jinmeng Zhang (Scientific Reports)
Abstract The extremely heavy rainstorm on September 16, 2011, in Nanjiang County, Sichuan Province, induced many accumulative landslides. Most of these slopes were 3 ~ 5 m thick, sliding along the soil‒bedrock interface, and the dip angle of the sliding bed was 10 ~ 20°. To study the reasons for and stability of this type of landslide, which mainly involved sliding along the soil‒bedrock interface, this paper took the Qiling Village landslide as an example and conducted shear tests on the sliding bodies, sliding zone soils, and bedrock interfaces with different moisture contents and numerically simulated the stability of the slope.The research results revealed that the shear strength of the sliding soil and the soil‒bedrock interface decreased with increasing moisture content. The shear strength of the sliding soil‒smooth bedrock interface was the smallest; therefore, the landslide slid along the sliding soil‒smooth bedrock interface. Under the action of heavy rainfall, the water level continued to rise, and the pore water pressure gradually increased. The coupling of pore water pressure and rainwater softening caused the Qiling Village landslide. The stability of the slope was greatly affected by pore pressure in the early stage of rainfall, and the influence of rainwater softening was greater in the later stage.